Perkembangan Musik Pop Indonesia - Irgi Rechansyah Gani; Kiki Zakiah Darmawan (Bandung Conference Series: Journalism, 2023)
Abstract. The phenomenon of reciting old Indonesian popular music from the 60-90s era is increasingly circulating everywhere, social media timelines, cafes, and many other unique mediums are widely listened to by Gen Z who incidentally were not born or even experienced the era that music first appeared. However, one thing that is missing from the phenomenon of the glittering Indonesian pop music today is the ongoing debate about what pop music really is, what underlies it's success. This study examines audience reception as readers of the book "From Ngak Ngik Ngok to Dheg Dheg Plas" to explore readers' understanding of the history and development of pop music in Indonesia. This research has a focus on examining how audience reception of the history of the development of Indonesian pop music in the book "From Ngak Ngik Ngok to Dheg Dheg Plas". The data were analyzed qualitatively using the reception analysis method through observation and interviews with readers. The results of this study indicate the hypothetical position of a number of informants. All informants occupy a dominant hegemonic position, 1 of a number of informants occupies a negotiating position, and none of the informants occupies an oppositional position. This evidence contains 4 aspects of knowledge discussed in the book From Ngak Ngik Ngok to Dheg Dheg Plas, and the informant claimed to have knowledge, especially in terms of state intervention in Indonesian pop music in the decade of the 60s. The informant admitted that after reading the book, his attitude changed and he liked Indonesian pop music in terms of strengthening the identity of a pop music lover, feeling validated as a pop music lover. Keywords: History, Pop Music, Communication. Abstrak. Fenomena lantunan musik populer lawas Indonesia era 60-90an kian berseliweran dimana-mana, linimasa media sosial, café, dan banyak medium lainnya yang uniknya banyak didengarkan oleh Gen Z yang notabene tidak lahir atau bahkan mengalami era musik-musik itu pertama kali muncul. Namun satu hal yang luput dari fenomena kemilaunya musik pop Indonesia saat ini adalah perdebatan yang tiada hentinya mengenai apa sebenarnya musik pop, apa yang melandasi musik-musik itu berjaya. Penelitian ini mengkaji resepsi khalayak sebagai pembaca buku “Dari Ngak Ngik Ngok ke Dheg Dheg Plas” untuk menggali pemahaman pembaca mengenai sejarah dan perkembangan musik pop di Indonesia. Penelitian ini memiliki fokus untuk meneliti bagaimana resepsi khalayak tentang sejarah perkembangan musik pop Indonesia dalam buku “Dari Ngak Ngik Ngok ke Dheg Dheg Plas”. Data dianalisis secara kualitatif dengan metode analisis resepsi melalui hasil observasi dan wawancara pembaca. Hasil dari penelitian ini menunjukkan posisi hipotekal sejumlah informan. Semua informan menempati posisi hegemoni dominan, 1 dari sejumlah informan menduduki posisi negosiasi, dan tidak ada satupun informan yang menduduki posisi oposisi. Bukti ini memuat 4 aspek pengetahuan yang dibahas dalam buku Dari Ngak Ngik Ngok ke Dheg Dheg Plas, dan informan mengaku mendapat pengetahuan terutama dalam hal intervensi negara terhadap musik pop Indonesia pada dekade 60-an. Informan mengaku mengalami perubahan sikap setelah membaca buku tersebut menambah rasa suka terhadap musik pop Indonesia dalam hal merperteguh identitas penyuka musik pop, merasa tervalidasi, sebagai penyuka musik pop. Kata Kunci: Sejarah, Musik Pop, Komunikasi.